A Review on Fabrication and Printing of Carbon Fiber-Reinforced Composite Filaments using FDM Process - Naidu, A. Lakshumu; Kumar, K. Himanth; Kumar, G. Ramesh; Vedavathi, L.; Kumar, J. Naveen; Rao, G. Shanmukha; Kalyan, N. Pavan (International Journal of Membrane Science and Technology, 2023)
This review aims to provide a comprehensive overview of the fabrication and printing of Carbon Fiber-Reinforced composite filaments using the FDM process. Fused Deposition Modelling (FDM) or Fused Filament Fabrication (FFF) is an Additive Manufacturing technology that uses the idea of melting the material and depositing it layer by layer. The filament for this is usually prepared by mixing the metal powder in a polymer. The material extrusion method is the preferred way to fabricate the 3D printed filament. In this article, the main processes behind various base polymers and combinations like PLA, ABS and PETG as base polymers and Carbon Fiber-Reinforced PLA, ABS and PETG as fillers have been discussed and various Mechanical Tests are also done by the 3D printed parts like Tensile, Compression, Hardness and Impact Test. It is concluded that the importance of Carbon Fiber composites in various industries, such as aerospace, automotive and consumer goods etc… the need for innovative manufacturing techniques like FDM.